KEPEMILIKAN INSTITUSIONAL, LEVERAGE DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Anggita Putri Cantika; Apit Susanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The aim of this study is to obtain empirical evidence about the effect of institutional ownership, composition of independent commissioners, composition of board of directors, audit committee, audit quality, size of the company, leverage, and profitability toward earnings management. This study used a sample of manufacturing companies that listed in Indonesia Stock Exchange (IDX) for three years, 2019 to 2021. The number of sample which collected with purposive sampling method is 74 companies with 218 data as a total. The study uses multiple regression method to examine the effect of independent variables on the dependent variable earnings management. The result of this study indicates that composition of independent commissioners and composition of board of directors have negative effect on earnings management, meanwhile leverage and profitability have positive effect on earnings management. On the other hand, other independent variables such as institutional ownership, audit committee, audit quality, and size of the company have no effect on earnings management.